Dimethyl fumarate ameliorates endotoxin-induced acute kidney injury against macrophage oxidative stress. Issue 1 (1st January 2021) - Zhou, Kejun; Xie, Mengyi; Yi, Shuli; Tang, Yun; Luo, Haojun; Xiao, Qiong; Xiao, Jun; Li, Yi
Abstract: Background: Characterized by macrophage infiltration, renal inflammation during septic acute kidney injury (AKI) reveals a ubiquitous human health problem. Unfortunately, effective therapies with limited side effects are still lacking. This study is aiming to elucidate the role of Dimethyl fumarate (DMF) in macrophages against oxidative stress of septic AKI. Methods: Balb/c mice were gavaged by 50 mg/kg DMF then injected with 10 mg/kg LPS by i.p. We examined LPS-induced renal dysfunction and histological features in murine kidneys. Raw264.7 macrophage cells were also treated with DMF and then induced by LPS. The mitotracker staining was used to follow mitochondria integrity by confocal microscopy. Flow cytometry measured the production of ROS by DCF-HDA and the expression of iNOS. Western blot detected the expression of Nrf-2 and Sirt1. Co-IP measured the interaction between Sirt1 and Nrf-2. Confocal microscopy observed the colocalization of Sirt1 and Nrf-2 in LPS-treated Raw264.7 macrophage cells. Results: DMF ameliorated murine LPS nephritis with reduced blood urea nitrogen and serum creatinine, as well as decreased the histological alterations compared to the normal control. DMF significantly inhibited the expression of iNOS and reduced the production of nitrite in Raw264.7 cells following LPS treatment. Our study also revealed the role of DMF in protecting against intracellular ROS accumulation and mitochondria dysfunction in LPS-induced nephritis. DMF facilitated colocalization and interaction between Sirt1 and Nrf-2 in LPS-treated cells. Conclusions: This study showed that DMF alleviated LPS-induced nephritis, indicating protective effects of DMF on macrophage against oxidative stress induced by LPS potentially involving Nrf-2-mediated pathway.